CD79B Y196 mutation is a potent predictive marker for favorable response to R‐MPV in primary central nervous system lymphoma. (7th December 2022) - Yamaguchi, Junya; Ohka, Fumiharu; Lushun, Chalise; Motomura, Kazuya; Aoki, Kosuke; Takeuchi, Kazuhito; Nagata, Yuichi; Ito, Satoshi; Mizutani, Nobuhiko; Ohno, Masasuke; Suzaki, Noriyuki; Takasu, Syuntaro; et al.
Abstract: Background: Rituximab, high‐dose methotrexate (HD‐MTX), procarbazine and vincristine (R‐MPV), has significantly prolonged the survival of patients with primary central nervous system lymphoma (PCNSL), but predictive factors for response to R‐MPV have not yet been investigated. Herein, we investigated the correlation of MYD88 L265P and CD79B Y196 mutations, which are the most frequently found molecular alterations in PCNSL, with prognosis of patients with PCNSL treated with R‐MPV. Methods: We investigated the long‐term clinical course and status of MYD88 and CD79B genes in 85 patients with PCNSL treated with R‐MPV or HD‐MTX treatment, and the correlation of these genetic mutations with prognosis. Results: R‐MPV achieved an excellent tumor control rate (61.6% and 69.9% of 5‐year progression‐free and overall survival rates, respectively). While MYD88 L265P mutation had no significant effect on survival, patients with CD79B Y196 mutations exhibited prolonged survival ( p < 0.05). However, the association of CD79B Y196 mutation with a better prognosis was not observed in the HD‐MTX cohort, which indicated that CD79B Y196 mutation was a predictive marker for a favorable response to R‐MPV. Furthermore, we established an all‐in‐one rapid genotyping system for these genetic mutations. Conclusions: In conclusion, CD79B Y196 mutation is a potent predictive marker for favorable response to R‐MPV in PCNSL. The rapid identification of MYD88 L265P and CD79B Y196 mutations can be helpful not only for the accurate molecular diagnosis of PCNSL but also for the prediction of response to R‐MPV. Abstract : CD79B Y196 mutation was a predictive marker for a favorable response to R‐MPV. We also established an all‐in‐one rapid genotyping system for this genetic mutation.